The The Influence of Extrinsic Motivation, Affective Commitment, and Job Satisfaction on Employee Performance During COVID-19 Pandemic - Purnomo, Trianto Panji; Wardhani, Nia Kusuma; Chaerudin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Objective – The purpose of this research is to conduct an analysis of the interrelationships by testing hypotheses regarding the positive and significant impact of extrinsic motivation factors, affective commitment, and job satisfaction on the performance of employees at SMK PGRI 109 Tangerang, especially in the COVID-19 pandemic situation. Methodology/approach – The method used in this research is a quantitative causal approach. A total of 78 individual employees participated as respondents in this study, and the sample was drawn from the entire population. Data was collected through questionnaires and analyzed using SmartPLS 3.2.9 software. Findings – The results of this research indicate that there is a strong and significant relationship between extrinsic motivation, affective commitment, job satisfaction, and employee performance at SMK PGRI 109 Tangerang. These findings are proven to be applicable both partially and comprehensively across all tested paths. Therefore, the hypotheses regarding the positive and significant influence of these three factors on employee performance can be accepted. Novelty/value – The findings provide deeper insights into the factors influencing employee performance, namely extrinsic motivation, affective commitment, and job satisfaction. With a better understanding of this relationship, management has the opportunity to design strategies aimed at enhancing employee performance through increasing extrinsic motivation, affective commitment, and job satisfaction. Moreover, this research also contributes novel insights to the literature on the relationships among the mentioned factors.